Attitudes of clinician educators towards interprofessional education and collaboration: Insights from two interprofessional scales. Issue 5 (3rd September 2017) - Ong, Sik Yin; Tan, Nigel C. K.; Knab, Mary S.; Farrell, Susan E.; Lim, Wee Shiong
ABSTRACT: The increasing complexity of healthcare needs underlines the growing importance of interprofessional education and collaborative practice (IPECP) in enhancing quality of patient care. In particular, clinician educators play an influential role in advocating IPECP. The primary goal of our exploratory pilot study is to explore 34 clinician educators' attitudes towards IPECP by using the adapted 14-item Attitudes Toward Health Care Teams Scale (ATHCTS) and 15-item Readiness for Interprofessional Learning Scale (RIPLS). Mean scores of ATHCTS and RIPLS were 3.81 (SD = 0.90) and 4.02 (SD = 0.79), respectively. Using exploratory factor analysis, we identified four factors: team value (ATHCTS), team efficiency (ATHCTS), teamwork and collaboration (RIPLS), and professional socialisation (RIPLS). The "team efficiency" factor on the ATHCTS scored lowest (factor mean = 3.49) compared with other factors (factor means = 3.87–4.08). Correlation analyses revealed that the "team efficiency" factor had small correlations with other factors ( r = −0.05–0.37). Our clinician educators valued IPECP in promoting teamwork and professional socialisation but they perceived IPECP to compromise efficiency. The issue of perceived inefficiency by clinician educators merits attention in order to promote wider implementation of IPECP.